Horizontes éticos : o cuidado como possibilidade de ser-no-mundo - Mello, Luciana Soares de (My University, 2014)
This entitled dissertation, Ethics horizons: the care as the possibility of being- in- the world, aims to reflect and establish exemplifications on the notion of care in Heidegger. The care will be interpreted from the perspective of the existential analytic levels, ontic and ontological, seeking to build ethical horizons through hermeneutic method. The interpretation of care is based on the theoretical ideias of Heidegger: Being and Time and the Letter about Humanism. We emphasize that it does not mean that other Heidegger´s ideas are not used in the course of these reflections, we only highlight the argumentative enphasis around the two mentioned ideias. The basis of argument arises from the following question: Is there the possibility to investigate the ethical horizons in your reflections about being? We started from the hypothesis that it is possible through existing studies about the theme. Given the striking feature of the Heidegger´s ideas, questions relating to unravel and be critical to society of their time within their way of being. This dissertation also seeks to establish the applicability of their theories in the context of contemporary society, in which the rise of science compartment, is still the dominant paradigm. In this context, we want to demonstrate the importance of Heidegger´s reflections within nature, interdisciplinary setting a dialogism between human knowledge, practical and theoretical because Heidegger realized that the lack of care was a stigma of the society in which he lived, in the twentieth century, when the war and the rise of technical sciences were the dominant paradigms. Given the fact that some findings, verified by Heidegger in the twentieth century, about the technological society, are still present nowadays, we see the importance of his reflections for a harmonious coexistence, affective and cooperative society.
A presente dissertação, Horizontes éticos: o cuidado como possibilidade de ser-no-mundo, tem o objetivo de refletir e estabelecer exemplificações sobre a noção de cuidado em Heidegger. O cuidado a ser interpretado parte de uma perspectiva da analítica existencial nos níveis, ôntico e ontológico, procurando construir horizontes éticos, através do método hermenêutico. A interpretação do cuidado tem como base teórica as obras de Heidegger: Ser e tempo e Carta sobre o humanismo. Ressaltase que, isso não significa que outras obras de Heidegger não sejam utilizadas no decorrer destas reflexões; apenas salientaremos a ênfase argumentativa em torno das duas citadas. A base argumentativa surge da seguinte indagação: Existe a possibilidade de averiguações de horizontes éticos em suas reflexões acerca do ser? Parti-se da hipótese de que são possíveis, por meio de estudos já existentes acerca da temática. Diante da característica marcante das obras de Heidegger, desvendarem questionamentos referentes ao ser e a crítica à sociedade do seu tempo no âmbito de seu modo de ser. Este trabalho dissertativo busca também estabelecer a aplicabilidade de suas teorizações no contexto da sociedade contemporânea, em que a ascensão da ciência compartimental, ainda é paradigma dominante. Nesta contextualização, quer-se demonstrar a importância das reflexões do pensador no âmbito da natureza, estabelecendo um dialogismo interdisciplinar entre os saberes humano, prático e teórico, pois Heidegger percebeu que a falta de cuidado foi um estigma da sociedade, em que ele viveu, no século XX, em que a guerra e ascensão das ciências técnicas eram os paradigmas dominantes. Diante do fato de que algumas constatações, verificadas pelo pensador, no século XX, acerca da sociedade tecnológica, ainda estarem presentes nos dias de hoje, percebe-se a importância de suas reflexões para um convívio harmônico, afetivo e cooperativo em sociedade.
Keywords: Heidegger, Martin, 1889-1976; Ética; Fenomenologia; Ontologia